The Combined Effect Of Red Ginger Oil And Kinesiotaping On Womac Score In Elderly Patients With Osteoarthritis - Syukkur, Achmad; Prihanto, Yafet Pradikatama (Universitas Tribhuwana Tunggadewi, 2024)
Osteoarthritis (OA) is a gradually worsening, non-inflammatory condition that affects the synovial joints, with its prevalence rising as people age. The initial symptoms often include joint pain during movement, which can limit mobility in older adults. This restriction in movement can lead to stiffness, reduced functional ability, and challenges in fulfilling daily tasks for the elderly. This study aims to analyze the effect of red ginger oil and kinesiotaping on pain, stiffness and functional ability using the WOMAC score instrument. This study is a Quasi Experiment study with a Nonequivalent sample technique (pretest and posttest) control group with a sample size of 60, divided into 4 groups, namely the red ginger oil group, the kinesiotaping group, the combined red ginger oil + kinesiotaping group, and the control group. The red ginger oil and kinesiotaping intervention was carried out for 7 days. The results showed that there was a simultaneous effect of red ginger oil administration (p-value 0.000; RSquare 0.669), kinesiotaping (p-value 0.000; R-Square 0.877) and a combination of red ginger oil kinesiotaping (p-value 0.002; R-Square 0.532). The use of red ginger oil and kinesiotaping interventions showed significant results or had an impact on the WOMAC score, making them promising alternative therapies for reducing the severity of osteoarthritis in the elderly